Port development strategy to enhance small scale fisheries (case study in Binuangeun fish landing site, Lebak-Banten) - Setiadi M Noor; Iin Solihin; Retno Muninggar; Treza Desri Winanda (Universitas Teuku Umar, 2025)
PPI Binuangeun plays a significant role in enhancing the fishing activities of local fishers and serves as the largest fish landing base (PPI) in Lebak Regency. Fish production at PPI Binuangeun fluctuates annually; in 2022, total production reached 2,268,503 kilograms with an estimated value of approximately IDR 37.84 billion. This study aims to formulate development strategies for the operational enhancement of PPI Binuangeun. A survey method was employed using purposive sampling to select respondents representative of the target population. The facility development analysis was conducted using a SWOT approach, supported by Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS) matrices. The IFAS analysis resulted in a score of 3.24, indicating that internal strengths outweigh weaknesses, while the EFAS score of 2.97 reflects significant external opportunities. Based on the SWOT quadrant analysis (Quadrant I - Aggressive Strategy), two priority strategies were identified: (1) enhancing service quality and infrastructure to support fishing operations, landings, auctions, and marketing (SO1); and (2) leveraging existing potential to develop port facilities to optimize production through effective management (SO2). Facility maintenance, infrastructure improvement, and capacity expansion are recommended to support the advancement of PPI Binuangeun